Peer review in Clinical Pharmacology using the 8-D Assessment - Woodcock, Barry G. (Int J Clin Pharmacol Ther, 2017)
The requirement for editors of clinical pharmacology journals to maintain an overview of the peer review process for manuscripts submitted can be facilitated by use of the 8-D Assessment. The 8-D Assessment comprises peer review criteria to determine if the:1. Design of the study, 2. Diagnoses employed, 3. Drug molecules involved, 4. Dosages applied, 5. Data collected, 6. Discussion of the findings, 7. Deductions made, and 8. Documentation are in accord with the objectives of the study and meet the requirements of evidence-based medicine. This tool, although easy to apply, requires a high level of clinical pharmacology expertise, especially in the fields of drug disposition, pharmacokinetics, and drug action.